Deficient Sleep in Mouse Models of Fragile X Syndrome - Saré, R. Michelle; Harkless, Lee; Levine, Merlin; Torossian, Anita; Sheeler, Carrie A.; Smith, Carolyn B. (Frontiers in Molecular Neuroscience, 2017)
In patients with fragile X syndrome (FXS), sleep problems are commonly observed but are not well characterized. In animal models of FXS (dfmr1 and Fmr1 knockout (KO) /Fxr2 heterozygote) circadian rhythmicity is affected, but sleep per se has not been examined. We used a home-cage monitoring system to assess total sleep time in both light and dark phases in Fmr1 KO mice at different developmental stages. Fmr1 KOs at P21 do not differ from controls, but genotype x phase interactions in both adult (P70 and P180) groups are statistically significant indicating that sleep in Fmr1 KOs is reduced selectively in the light phase compared to controls. Our results show the emergence of abnormal sleep in Fmr1 KOs during the later stages of brain maturation. Treatment of adult Fmr1 KO mice with a GABAB agonist, R-baclofen, did not restore sleep duration in the light phase. In adult (P70) Fmr1 KO/Fxr2 heterozygote animals, total sleep time was further reduced, once again in the light phase. Our data highlight the importance of the fragile X genes (Fmr1 and Fxr2) in sleep physiology and confirm the utility of these mouse models in enhancing our understanding of sleep disorders in FXS.